Effects of shock and Martian alteration on Tissint hydrogen isotope ratios and water content. (1st March 2017) - Hallis, L.J.; Huss, G.R.; Nagashima, K.; Taylor, G.J.; Stöffler, D.; Smith, C.L.; Lee, M.R.
Abstract: The Tissint meteorite, a picritic shergottite, fell to Earth in Morocco on the 18th of July 2011, and is only the fifth Martian meteorite witnessed to fall. Hydrogen isotope ratios and water contents are variable within different minerals in Tissint. Ringwoodite and shock melt pockets contain elevated D/H ratios relative to terrestrial values (δD = 761–4224‰). These high ratios in recrystallized phases indicate significant implantation of hydrogen from the D-rich Martian atmosphere during shock. In contrast, although olivine has detectable water abundances (230–485 ppm), it exhibits much lower D/H ratios (δD = +88 to −150‰), suggesting this water was not implanted from the Martian atmosphere. The minimal terrestrial weathering experienced by Tissint gives confidence that the olivine-hosted water has a Martian origin, but its high concentration indicates direct inheritance from the parental melt is improbable, especially given the low pressure of olivine crystallisation. Incorporation of a low δD crustal fluid, or deuteric alteration during crystallisation, could explain the relatively high water contents and low D/H ratios in Tissint olivine.